Pneumatic structures in the neck of the early cretaceous dicraeosaurid amargasaurus cazauisalgado and bonaparte, 1991 (sauropoda, diplodocoidea) from patagonia, Argentina - Windholz, Guillermo Jose (2020)
The presence of a complex pattern of pneumatization has been widely reported in several diplodocoid sauropods. Singularly, the degree of pneumaticity development in the axial skeleton of Dicraeosauridae is low when compared with other diplodocoid taxa. Here we report preliminary results obtained from CT scanning images and external osteological correlations of two cervical vertebrae taken from the holotype specimens of Amargasaurus cazaui (MACN-N 15), (a mid-cervical vertebra and a posterior cervical vertebra). The lateral surface of the centra of the cervical elements of MACN-N 15 bears deep and broad fossae. Also, the CT images show lateral fossae that are communicated with successive generations of small camerae, located at the vertebral centrum, constituting a camerate internal structure type, like in the posterior cervical vertebra of Pilmatueia faundezi Coria, Windholz, Ortega and Currie, 2019 (MLL-Pv-002). Conversely, a procamerate pattern was recognized in a mid-cervical vertebra of Pilmatueia (MLL-Pv-004) and in mid and posterior cervical vertebrae of Dicraeosaurus sp. Janensch, 1914 (HMN E14; HMN E27). It´s seems that Amargasaurus (MACN-N 15) was the form that achieved the highest degree of pneumatization within the dicraeosaurids from Gondwana. The CT scanning images presented here confirm previously suggested for Pilmatueia and other dicraeosaurd sauropods.